2012
DOI: 10.1002/ajp.22095
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Interactions between Primates, Birds, Bats, and Squirrels May Affect Community Composition on Borneo

Abstract: For several decades, primatologists have been interested in understanding how sympatric primate species are able to coexist. Most of our understanding of primate community ecology derives from the assumption that these animals interact predominantly with other primates. In this study, we investigate to what extent multiple community assembly hypotheses consistent with this assumption are supported when tested with communities of primates in isolation versus with communities of primates, birds, bats, and squirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The use of "community" in reference to a taxonomic group is especially evident in the primatology literature, where relationships between primate species are emphasized (e.g., competition, predator-prey, polyspecific associations) and interspecific interactions between primate and non-primate species are largely overlooked (Kamilar and Beaudrot 2013;Reed and Bidner 2004). The limited research that has focused on the relationships between primates, birds, bats, squirrels, and ruminants (e.g., Beaudrot et al 2013a;Beaudrot et al 2013b;Emmons 1980;Emmons et al 1983;Garber and Sussman 2005;Gautier-Hion et al 1980;Poulsen et al 2003), has shown that these non-primate species are important potential competitors of primates and should not be ignored when examining the behavioral ecology of a primate species.…”
mentioning
confidence: 98%
“…The use of "community" in reference to a taxonomic group is especially evident in the primatology literature, where relationships between primate species are emphasized (e.g., competition, predator-prey, polyspecific associations) and interspecific interactions between primate and non-primate species are largely overlooked (Kamilar and Beaudrot 2013;Reed and Bidner 2004). The limited research that has focused on the relationships between primates, birds, bats, squirrels, and ruminants (e.g., Beaudrot et al 2013a;Beaudrot et al 2013b;Emmons 1980;Emmons et al 1983;Garber and Sussman 2005;Gautier-Hion et al 1980;Poulsen et al 2003), has shown that these non-primate species are important potential competitors of primates and should not be ignored when examining the behavioral ecology of a primate species.…”
mentioning
confidence: 98%
“…Interestingly, this is not the case for primates of the Sunda Shelf. In comparable analyses of Bornean communities, Beaudrot and colleagues found patterns consistent with the interpretation that while frugivorous primate species did co‐occur in the same communities, competition with birds, bats, and squirrels was more severe, potentially leading to competitive exclusion between certain primates and nonprimate vertebrates. Evidence of competitive exclusion was strongest between invertebrate‐eating primates and other taxa, especially birds and squirrels.…”
Section: What Do We Know?mentioning
confidence: 65%
“…Understanding the processes behind the assembly (Diamond 1975) and the structure of modern (Brown et al 2000;Millien-Parra and Loreau 2000;Gotelli and McCabe 2002;Feeley 2003;Morris 2005;Pennington et al 2006;Emerson and Gillespie 2008;Ernest et al 2008;Stegen and Swenson 2009;Abu Baker and Patterson 2010;Pavoine and Bonsall 2011;Belmaker and Jetz 2012;HilleRisLambers et al 2012;Beaudrot et al 2013;Cantalapiedra et al 2014) and past (Riddle 1998;Costeur et al 2004;Davis 2005;McGill et al 2005; This article is a contribution to the special issue BOld worlds, new ideas. A tribute to Albert van der Meulen^.…”
Section: Introductionmentioning
confidence: 99%